-5x+2=-1

Simple and best practice solution for -5x+2=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x+2=-1 equation:


Simplifying
-5x + 2 = -1

Reorder the terms:
2 + -5x = -1

Solving
2 + -5x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -5x = -1 + -2

Combine like terms: 2 + -2 = 0
0 + -5x = -1 + -2
-5x = -1 + -2

Combine like terms: -1 + -2 = -3
-5x = -3

Divide each side by '-5'.
x = 0.6

Simplifying
x = 0.6

See similar equations:

| 30.6/1.068 | | 22=34-b | | 7x-5=3+4x | | 28=b(b-3) | | 2/7+2/7=-4/5v-3/5v | | sx-5=9 | | 2(2x+4)=3x+12 | | 18x^2-132x+242=0 | | 8(x+1)-11=53 | | x+0.068x= | | x+x+5+2(x+5)=431 | | 3x+-14=x | | a^2-15a-40=0 | | 33-4x=2x-3 | | 6y=4-12 | | 3a/4-7/4=4a/3+5/3 | | 3x+10=17+2x | | x+0.068= | | m^2+7m-12= | | 7/3=2w | | 4(x+1)-11=53 | | 5(x+1)-11=53 | | -6(x+1)-11=53 | | 60=-16x^2+85x | | x+2/3-1/2=x/3-2(x-2)/3 | | -3x-3(-5x-17)=17 | | -4h+16=22+2 | | 12+2(3p-4)=22 | | 11-6m-20=20-5m | | 5x+3=6x-14 | | 3b+2(b-3)=91.50 | | 8x-(-2+3)=11 |

Equations solver categories